ابتكارات التكنولوجيا المالية و دورها في تطوير أداء البنوك الإسلامية العربية - شاوي, شافية; مطرف, عواطف; بومود, إيمان (جامعة الوادي - University of Eloued, 2020)
يهدف هذا البحث إلى إلقاء الضوء على التأثير الإيجابي لابتكارات التكنولوجيا المالية في تطوير أداء البنوك الإسلامية العربية، حيث تمكن التقنيات الرقمية الجديدة هذه البنوك من سهولة التعريف بمنتجاتها وخدماتها المالية، وتقديم خدماتها بكفاءة كبيرة وجودة عالية ما يعكس قدرتها على التنافس في السوق المالية. فوجب على البنوك الإسلامية العربية تبني التكنولوجيا المالية، وذلك بهدف مواكبة عصر الرقمنة والاستفادة من الخدمات التي تقدمها شركات التكنولوجيا المالية، خاصة في ظل اعتماد البنوك على الأنظمة القديمة والتقليدية، في الوقت الذي ينطوي فيه تحول البنوك إلى منصات أعمال رقمية على الكثير من الفرص. ولقد استخدمت بعض البنوك الاسلامية كبنك الامارات الإسلامي تكنولوجيا البلوكشين في تحقيق شروط التمويل المعقدة، والمعاملات المتوافقة مع الشريعة الإسلامية و البدائل الإسلامية لاسيما وأنّ البلوكشين يمكن أن تساعد في عمليات معرفة العميل وأتمتة العمليات والمدفوعات الصغيرة. كما تعتبر التجربة البحرنيّة ألكو البحرين للتكنولوجيا المالية أول تجربة على مستوى العالم، والتي تهدف إلى استعادة نمو صناعة البنوك الإسلامية وتجهيزها لنقلة نوعية في القطاع المصرفي نتيجة ابتكارات التكنولوجيا المالية. This research aims to shed light on the positive impact of financial technology innovations in the development of Arab Islamic bank, where new digital technologies enable these banks to easily identify their financial products and services, and provide their services with great efficiency and high quality reflecting its ability to compete in the financial market. Arab Islamic banks must adopt financial technology, with the aim of keeping pace with the era of digitization and taking advantage of the services provided by financial technology companies, especially as banks rely on old and traditional systems, while involving the transformation of banks into digital business platforms on a lot of opportunities. Some Islamic banks, such as Emirates Islamic Bank, have used blockchain technology to achieve complex financing requirements, Sharia-compliant transactions and Islamic alternatives, especially since blockchain can help with customer knowledge processes and automate processes and small payments. Alco Bahrain's Bahrain Financial Technology Experience is also the first in the world to restore the growth of the Islamic banking industry and equip it for a qualitative shift in the banking sector as a result of financial technology innovations.
Innovations of Financial Technology and its Role in Improving the Performance of Arab Islamic banks
مقال
Keywords: تكنولوجيا ماليّة ؛ بنوك إسلامية ؛ ألكو البحرين ؛ تكنولوجيا البلوكشين; Financial Technology, Islamic Banks; Alco Bahrain; Blockchain Technology.